2012
DOI: 10.1371/journal.pone.0040876
|View full text |Cite
|
Sign up to set email alerts
|

Higher Levels of ATGL Are Associated with Exercise-Induced Enhancement of Lipolysis in Rat Epididymal Adipocytes

Abstract: BackgroundIn adipose cells, adipose triglyceride lipase (ATGL) catalyzes the first step in adipocyte triacylglyceride hydrolysis, thereby regulating both basal and hormone-stimulated lipolysis. However, little is known about the molecular mechanism(s) underlying habitual exercise-induced adaptive modulation of ATGL in white adipocytes via alteration in transcription regulator and lipolytic cofactors.Methodology/Principal ResultsMale Wistar rats were randomly divided into 2 groups a sedentary control group (CG)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 45 publications
2
32
0
Order By: Relevance
“…Further, the role of adipose triglyceride lipase (ATGL) has long been investigated for its regulation by insulin, expression alterations during obesity as well as exercise-induced enhancement for lipolysis in adipocytes. Thus, exercise likely induces a panoply of events that sculpt the lipidome of scWAT and BAT tissue (Burstein et al, 1992; Koivisto and Yki-Jarvinen, 1987; Stanford et al, 2015b),(Jocken et al, 2007; Kershaw et al, 2006; Ogasawara et al, 2012). Together, these studies provide a rationale to study these phospholipases in the regulation of phospholipids and mitochondrial function in response to exercise (Jocken et al, 2007; Kershaw et al, 2006; Mancuso et al, 2010; Ogasawara et al, 2012); future studies will focus on exercise-induced regulation of these phospholipases and how they can potentially contribute to insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the role of adipose triglyceride lipase (ATGL) has long been investigated for its regulation by insulin, expression alterations during obesity as well as exercise-induced enhancement for lipolysis in adipocytes. Thus, exercise likely induces a panoply of events that sculpt the lipidome of scWAT and BAT tissue (Burstein et al, 1992; Koivisto and Yki-Jarvinen, 1987; Stanford et al, 2015b),(Jocken et al, 2007; Kershaw et al, 2006; Ogasawara et al, 2012). Together, these studies provide a rationale to study these phospholipases in the regulation of phospholipids and mitochondrial function in response to exercise (Jocken et al, 2007; Kershaw et al, 2006; Mancuso et al, 2010; Ogasawara et al, 2012); future studies will focus on exercise-induced regulation of these phospholipases and how they can potentially contribute to insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…FA mobilization from WAT is regulated by the activity of hormone-sensitive lipase (HSL), monoglyceride lipase (MGL) and adipose triglyceride lipase (ATGL) [39]. Since exercise promotes lipolysis from adipocytes by activating HSL and ATGL [40, 41], exercise-induced hypotrophy of adipocytes is, at least in part, responsible for the reduction of WAT mass in obese individuals. However, it remains uncertain whether endurance exercise regulates adipogenesis by altering adipogenic gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Importantly, analyses of NEFA rate of appearance (Ra) [4][5][6] during exercise revealed that this variable was significantly reduced as a result of training, which is also in support of a reduction in WAT lipolysis with endurance training. However, at odds with these findings are the results of studies measuring catecholamine-stimulated glycerol release in isolated adipocytes from humans [7][8][9][10][11] and rats, [12][13][14][15] which report increased WAT lipolysis after a period of endurance training. Additional studies have reported lipolysis to be either reduced in isolated rat adipocytes 16 or unaltered when assessed in situ by the microdialysis technique in human WAT 17 following a period of endurance training.…”
Section: Introductionmentioning
confidence: 99%